Developing A Penang Cultural Tourism Website Prototype: A User-Centred Design Approach - Goh Chu Hiang (Wacana Seni Journal of Arts Discourse, 2008)
Most Malaysian tourism website designs are text-heavy. They deliver information but reflect little regard for usability. Malaysian web designers and developers are unaware of the importance of user-centred web designs necessary in order to promote cultural tourism. This paper details the development of a Penang cultural tourism website prototype that employs a user-centred design approach. The website aims to disseminate information about the multicultural traditions of Penang, which include the performing arts, crafts and festivals. In the use of personas, this article seeks to examine the effectiveness and functionality of web pages and subsequently develop a Penang cultural tourism website prototype.